Multivariate analysis of causal factors influencing accuracy of guided implant surgery for partial edentulism: a retrospective clinical study - Atsushi Matsumura; Tamaki Nakano; Shinji Ono; Akihiro Kaminaka; Hirofumi Yatani; Daijiro Kabata (SpringerOpen, 2021)
Abstract Background In dental implant treatment, the placement position of the implant body is important. The hypothesis is that there are factors that have a greater impact than the factors that have been studied so far. Material and Methods The deviation between planned and actually placed implants was measured three-dimensionally by modified treatment evaluation method in 110 patients who underwent implant placement with guided surgery for partial edentulism. Ten factors that seemed to affect errors in placement were selected: the type of tooth, type of edentulism, distance from the remaining teeth, the type of implant, implant length, number of implants, method of guidance, the number of teeth supporting the surgical guide, number of anchor pins, and presence or absence of a reinforcement structure. The effect of each factor that corrected each confounding was calculated using multivariate analysis. Results In this study, 188 implant bodies were set to target, and the errors measurement data of the implant position were as follows: average Angle, 2.5 ± 1.6° (95% CI 2.25-2.69); Base, 0.67 ± 0.37 mm (95% CI 0.62-0.72); and Apex, 0.92 ± 0.47 mm (95% CI 0.86-0.98). As the result of multivariate analysis, larger errors were present in the partially guided group than the fully guided group. The number of teeth supporting the surgical guide significantly influenced the error in placement position. The error caused by the number of anchor pins was significantly different for the Angle. Similarly, the presence of the reinforcement structure influenced the error significantly for the Angle. Conclusions It was suggested that the smaller errors could be present by performing guided surgery with full guidance and devising the design of the guide such as the number of teeth supporting the surgical guide, the setting of the anchor pin, and the reinforcement structure.